DRAFTING OF THE CERTIFICATION SCHEME FOR THE SECURITY AND PUBLIC ORDER ADVISORS (BHABINKAMTIBMAS) - Tri Setianingsih; Asrofi Asrofi (DIA: Jurnal Administrasi Publik, 2025)
The Indonesian National Police has a strategic role in maintaining order and security in Indonesia. Bhabinkamtibmas, as the front guard in community development, requires increased competence to overcome the expertise gap and foster public trust. This study aims to develop a Bhabinkamtibmas certification scheme that guides implementing certification for Bhabinkamtibmas to obtain formal recognition of their competence. A qualitative approach was used in this study, data collection through Focus Group Discussion (FGD) and document analysis. As a result, the proposed certification scheme includes various competency units related to the main tasks of Bhabinkamtibmas in the Special Work Competency Standards (SK3) of Bhabinkamtibmas, which are designed to ensure competence according to the standards required in the field. The development of this scheme is expected to improve the quality of Polri's human resources, especially Bhabinkamtibmas, and help it achieve superior human resources in facing the challenges of the Police 4.0 era.